Surface Modification of Ferritic Stainless Steel SS 430 with Cobalt-Based Coating For SOFC Iinterconnect Applications Using Thermal Spray Method - Yoga Perwata, Mohamad
Technological development of solid oxide fuel cell currently allows to be operated at lower temperatur of about 650-850 ????C. In this temperatur range, the use of ceramics materials in the interconnect can be replaced with metallic material. However, these materials are prone to the formation of Cr2O3 oxide layer at high temperature. Cr2O3 oxide reacts with the fuel to produce volatile Cr that will settle on the cathode and degrade the performance of SOFC. To solve these problem, we have developed the coating method using flame spray technique. In this study ultrabond 50000 mixed with cobalt powder with weight ratio (% wt 80: 20) was deposited on ferritic stainless steel surface using flame spray technique with torch distance is 30 cm and perpendicular to the substrate surface. The coated specimens will be oxidized in the furnace with air atmosphere (PO2 = 0.21 atm) at 800 oC for 1, 2, and 4 days. XRD results shown that the oxide layer was formed on the 4 days oxidized specimen surface. The oxide were identified as Co3O4 and NiO. The rate of oxidation of this layer is equal to 4x10-15 gr2/mm2s